2015
DOI: 10.4103/0976-9668.160033
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic and biologic mode of reattaching incisor fracture fragment utilizing glass fiber post

Abstract: Trauma to the anterior teeth affects the esthetic and psychological well-being of the patient. Advancement in the adhesive dentistry has facilitated the restoration of the coronal tooth fractures by minimally invasive procedures when the original tooth fragment is available. Reattachment of fractured fragment offers immediate treatment with improved preponderant aesthetics and restoration of function. Here, we describe a case of complicated fracture of the maxillary left immature permanent central incisor, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…These include using a circumferential bevel before reattaching [ 13 , 14 ], placing a chamfer at the fracture line after bonding [ 15 ], using a V-shaped enamel notch [ 16 ] or a groove with shoulder [ 17 ], and placing an internal groove or a superficial contour over the fracture line, while some authors have reported on the use of bonding with no additional preparation [ 18 , 19 ]. Manju et al [ 20 ] described a case of complicated fracture of the maxillary left immature permanent central incisor that was treated endodontically followed by esthetic reattachment of the fractured fragment using a glass fiber post. In addition, some authors have reported that porcelain laminate can be used to reinforce the fractured fragments that are bonded to each other.…”
Section: Introductionmentioning
confidence: 99%
“…These include using a circumferential bevel before reattaching [ 13 , 14 ], placing a chamfer at the fracture line after bonding [ 15 ], using a V-shaped enamel notch [ 16 ] or a groove with shoulder [ 17 ], and placing an internal groove or a superficial contour over the fracture line, while some authors have reported on the use of bonding with no additional preparation [ 18 , 19 ]. Manju et al [ 20 ] described a case of complicated fracture of the maxillary left immature permanent central incisor that was treated endodontically followed by esthetic reattachment of the fractured fragment using a glass fiber post. In addition, some authors have reported that porcelain laminate can be used to reinforce the fractured fragments that are bonded to each other.…”
Section: Introductionmentioning
confidence: 99%
“…Whenever possible, the most commonly recommended technique is autogenous or homogenous fragment bonding [ 9 , 10 ]. Fragment bonding is a procedure that can be labeled as “biological restoration,” consisting of the use of fragments of the fractured tooth (autogenous bonding) or fragments obtained from an extracted tooth (homogenous bonding) [ 11 , 12 ]. This technique allows reestablishment of the dental element with its original characteristics and the maintenance of occlusion in natural teeth and is inexpensive and has a positive psychological effect, since the social and emotional well-being of the patient and their family is restored [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Os avanços na odontologia adesiva oferecem opções variadas para recolocação de fragmentos fraturados com base na amplitude, na direção e na gravidade da fratura (MANJU et al, 2015).…”
Section: Introductionunclassified